PEMBELAJARAN IPS SEJARAH DAN SIKAP NASIONALISME DALAM ERA GLOBALISASI - Bauto, Laode Monto (JURNAL PENDIDIKAN ILMU SOSIAL, 2013)
The incidence of individualist attitudes and reduced social kepedlian and others. It all becomes an indicator of the lunturnya attitude of nationalism, especially among the younger generation successor to relay the struggle of a nation. Through teaching history students capable of developing competence to think in chronological order and having knowledge about the past that can be used to understand and explain the developmental process and change people and diversity socio-culture in order find and cultivate identity nation in the society the world. Teaching history asked students realizes the diversity life experiences in each society and the way different viewpoint against its past to understand the present and build knowledge and understanding to face the future. Thus probate Soekarno â€œ jas redâ€Â  must remain we amalkan. As is expression philosopher mulan kundera stating that if will destroy a nation, then destory first its history should let us think about.Keywords :Pembelajaran, sikap, nasionalisme, globalisasi